A New Bioactive Compound From the Marine Sponge-Derived Streptomyces sp. SBT348 Inhibits Staphylococcal Growth and Biofilm Formation - Balasubramanian, Srikkanth; Skaf, Joseph; Holzgrabe, Ulrike; Bharti, Richa; Förstner, Konrad U.; Ziebuhr, Wilma; Humeida, Ute H.; Abdelmohsen, Usama R.; Oelschlaeger, Tobias A. (Frontiers in Microbiology, 2018)
Staphylococcus epidermidis, the common inhabitant of human skin and mucosal surfaces has emerged as an important pathogen in patients carrying surgical implants and medical devices. Entering the body via surgical sites and colonizing the medical devices through formation of multi-layered biofilms leads to refractory and persistent device-related infections (DRIs). Staphylococci organized in biofilms are more tolerant to antibiotics and immune responses, and thus are difficult-to-treat. The consequent morbidity and mortality, and economic losses in health care systems has strongly necessitated the need for development of new anti-bacterial and anti-biofilm-based therapeutics. In this study, we describe the biological activity of a marine sponge-derived Streptomyces sp. SBT348 extract in restraining staphylococcal growth and biofilm formation on polystyrene, glass, medically relevant titan metal and silicone surfaces. A bioassay-guided fractionation was performed to isolate the active compound (SKC3) from the crude SBT348 extract. Our results demonstrated that SKC3 effectively inhibits the growth (MIC: 31.25 µg/ml) and biofilm formation (sub-MIC range: 1.95-<31.25 µg/ml) of S. epidermidis RP62A in vitro. Chemical characterization of SKC3 by heat and enzyme treatments, and Mass Spectrometry (HRMS) revealed its heat-stable and non-proteinaceous nature, and high molecular weight (1258.3 Da). Cytotoxicity profiling of SKC3 in vitro on mouse fibroblast (NIH/3T3) and macrophage (J774.1) cell lines, and in vivo on the greater wax moth larvae Galleria melonella revealed its non-toxic nature at the effective dose. Transcriptome analysis of SKC3 treated-S. epidermidis RP62A has further unmasked its negative effect on central metabolism such as carbon flux as well as, amino acid, lipid and energy metabolism. Taken together, these findings suggest a potential of SKC3 as a putative drug to prevent staphylococcal DRIs.